Conhecimento tradicional e usos do umbuzeiro (Spondias tuberosa Arruda) por comunidades rurais do semiárido paraibano, Nordeste do Brasil - Paodjuenas, Rogério (2018)
The umbuzeiro (Spondias tuberosa Arruda) belonging to the family Anacardiaceae, is one of the most important and native species of great importance in the semiarid region of Northeast Brazil, due to its versatility. Many traditional knowledge about the uses of plants in the semiarid are being lost or forgotten. The present study registered the traditional knowledge and uses of this species, by residents of five rural communities of Paraíba, Northeast Brazil, being the communities of São Francisco, Coelho, Várzea Alegre, Capivara and Santa Rita, through a semi structured ethnobotanical questionnaire. All household heads were interviewed, representing 100 % of all households in the communities. In the São Francisco community, 255 citations were registered (102 men and 153 women), in Coelho, 64 citations were registered (33 men and 31 women). In Várzea Alegre, 68 citations were registered (35 men and 33 women), in Santa Rita, 208 citations were used (101 men and 107 women) and in the Capivara community 339 citations (158 men and 181 women), totaling 934 citations, 505 of which were made by women and 429 by men. The most relevant categories were: food (146 citations), forage (65 citations) and medicinal (20 citations) in the city of Cabaceiras. In Remígio, food (38 citations) and forage (13 citations). In São Mamede, the categories of food (52 citations) and forage (12 citations) were highlighted. In Solânea the category food (154 citations), forage (91 citations) and shadow (30 citations). In the city of Congo, the categories of food (136 citations) and forage (40 citations of use) were highlighted. In Várzea Alegre the use of the in natura fruit was present in 59.62 % of the citations, preceding the umbuzada with 15.38 %. In the community of Santa Rita, the use of the fruit in natura was present in 38.97 % of the citations, the umbuzada in 32.35 %. In the category of forage, only the uses of leaves and fruits were registered, representing in the communities of Capivara (26.84 %), São Francisco (25.49 %), and Coelho (20.31 %). In terms of logging, the fuel category was recorded, with Capivara (7.67 %), São Francisco (5.49 %) and Coelho (4.69 %), followed by Santa Rita (3.85 %) and Várzea Alegre (1.47 %). In the technology category, in the communities of Coelho (4.69 %), Capivara (0.59 %) and São Francisco (0.39 %). For the medical category, they were registered in the community of São Francisco (7.84 %), Santa Rita (2.88 %), Capivara (2.65 %) and Várzea Alegre (1.47 %). In the São Francisco, Capivara and Santa Rita communities women know more about the uses attributed to S. tuberosa than men, being 60 %, 53.40 % and 51.44 %, respectively. In the communities of Várzea and Coelho, the men showed greater knowledge than the women being quantified, 48.52 % and 48.43 %, respectively. The populations of the communities, Capivara, Coelho, Santa Rita, São Francisco and Várzea Alegre demonstrated that the umbuzeiro (S. tuberosa Arruda) is extremely important for its daily life due to the varied uses and categories attributed to the species.